Forecasting financial stress and the economic sensitivity in CEE countries - Maciej Krzak; Grzegorz Poniatowski; Katarzyna Wąsik (Center for Social and Economic Research (CASE), 2014)
This paper presents forecasts for the Financial Stress Index (FSI) and the Economic Sensitivity Index (ESI) for the period 0 - 0 5 for six countries in the region, namely the Czech Republic, Estonia, Hungary, Latvia, Lithuania and Poland. It is a continuation of the endeavor to construct synthetic indices measuring financial stress and economic sensitivity for twelve Central and East European countries using the Principal Component Analysis. In order to obtain forecasts of the FSI, we estimated Vector Autoregression (VAR) models on monthly data for the period 00 - 0 separately for all the countries. Using quarterly historical values of ESI and FSI, we estimated Dynamic Panel Data Model for the complete sample of countries. Parameters of the model were later used for forecasting the ESI. Obtained results suggest that the FSI will start to rise in 0 in the Czech Republic, Lithuania, and Estonia. For Latvia and Hungary, we observed a conversion in the trend, i.e. at the beginning of 0 5, when the index should start to fall. According to our forecasts, the ESI will be rising in the next two years, except for Hungary, where we predict a continuous decrease in economic sensitivity.
Keywords: 330; financial stress; economic sensitivity; economic indicators; Central and Eastern Europe